Peranan Keteladanan Guru Pai Dalam Pembinaanakhlak Mulia Peserta Didik Di Madrasah Aliyah Al-Ma’arif Bilae Kec. Awangpone - Agussalim, Agussalim (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This research to studying the results showed that The role of modeling of teachers of Islamic Education in the character building starts on the students include Madrasah Aliyah Al-Ma’arif Bilae Kecamatan Awangpone in Bone Regency.The type of research used is qualitative with the research approach used is religious, phenomenological, pedagogic, and sociological approach. The data sources of this study consist of teachers PAI, Principal, Vice principal of student, supervisors extracurricular activities, and learners. Furthermore, data collection methods used are observation, interviews, and documentation. Then, the technique of analysis and interpretation of research data using Miles and Huberman analysis model through three stages, namely; data reduction, data presentation, conclusion, and data validity testing. The results showed that The role of modeling of teachers of Islamic Education in the character building starts on the students include; a) program (group learning system); b) program (night prayer / duha); and c) Tadarrus and rote program of the Qur'an.